Brief reflections on Constitutional Litigation with particular reference to the Peruvian Case - Sáenz Dávalos, Luis R. (2016)
These reflections, necessarily brief, try to offer our introductory overview of the subject, facing what is meant and, of course, expect that discipline in our midst. The have exposed countless times and over the years we have in the teaching life. This time, the present writing without any claim that is not offered by a simple opinion piece. The reader point to the relevance or otherwise of them.